Falls from a balcony while intoxicated: a new injury trend among young adults? - Kathryn B. Schaffer; Gary Schwendig; Fady Nasrallah; Jiayan Wang; Jess F. Kraus (BMC, 2019)
Abstract Background Unintentional falls from heights, including balconies, result in life threatening traumatic injury. Alcohol, when combined with environmental factors and poor judgement, can potentially lead to fatal outcomes. One trauma center's registry identified a group of young adults falling from balconies and we investigated the role of alcohol. Methods Hospital trauma service admissions from 2010 through 2017 were reviewed for unintentional falls from heights. Suicide attempts and unintentional falls off ladders or roofs were excluded. Data were obtained from trauma registry and medical record review, as well as social work service interviews. Results Falls from heights comprised 4.8% of injuries treated at our trauma center during the eight-year study period with 98.5% admitted. Of patients admitted because of falls, 10.3% (55/532) were from a balcony. The majority of this group of patients was male and 19-29 years old (67%). Of patients with a blood alcohol concentration (BAC) determination, 62% had a positive BAC upon hospital admission with an average of 0.20 g/dL among those 34 patients. No gender differences were evident for alcohol use. Seven of the eight patients under the legal drinking age of 21 years were a subgroup with high alcohol use as compared with patients 21 years and older (p = 0.099). Ninety-four percent of falls occurred at residential locations such as dormitories or apartment complexes, often during a social event. Backward falls off railings and attempts to jump to adjoining balconies were common. Head, thorax/abdomen, and extremity fractures were common, with an average injury severity score (ISS) of 16. Average length of hospital stay was 8 days. Most patients (67%) were discharged home after hospital stay, but 21% were transferred to inpatient rehabilitation or skilled nursing facilities. There were two deaths. Conclusions Falls from balconies among young adults occur in our area yet the true frequency of these events remain unknown. Occurrence was most common among underage drinkers. Generalization is difficult with this small sample, yet high risk behaviors and environmental factors were evident. It is imperative that educational programs focus on this population with collaborative prevention efforts focused on the dangers of, and increased risk of injury associated with the balcony environment.